State anxiety is associated with hormonal, cardiovascular, and sleep parameters in Finnish postmenopausal women - Rimpilä, Ville; Vahlberg, Tero; Valli, Katja; Saaresranta, Tarja (Elsevier BV, 2025)
Objective To investigate how a range of variables, both physiological (sleep architecture, serum follicle-stimulating hormone (S-FSH), anthropometric and blood pressure measures) and non-physiological (stressful life events, education), are associated with symptoms of distress, anxiety, and depression from premenopause to postmenopause and at postmenopause. Methods We recruited 64 women (ages 45-47). Data were derived from an in-house questionnaire, the Brief Symptom Inventory, State-Trait Anxiety Inventory, Beck Depression Inventory, a sleep questionnaire, physiological measurements, and polysomnography at baseline and at ten-year follow-up. Results During the follow-up, an increase in weight was associated with an increase in anxiety as recorded by the Brief Symptom Inventory (p = 0.012, R-2 = 0.117). Cross-sectionally, at postmenopause, state anxiety was associated with an increase in blood pressure and S-FSH, delayed REM sleep, and the use of menopausal hormone therapy (p(STAI-S) < 0.001, R-2 = 0.343). Distress and depressive symptoms were associated with stressful life events and a lower level of education but also with an increase in diastolic blood pressure and use of hormone therapy (p(BSI) < 0.001, R-2 = 0.328 and p(BDI) < 0.001, R-2 = 0.312). Sleep disruptions were associated with psychological symptoms but vasomotor symptoms were not. Conclusions The change in psychological symptoms during the follow-up was modest. At postmenopause, distress and depressive symptoms were associated with a range of physiological and non-physiological parameters, but state anxiety only with physiological parameters. At postmenopause, psychological symptoms were more sensitive to sleep disruptions than were vasomotor symptoms.